Context, visibility and control: Contesting the objectivity of visual (video) records of police‐citizen interactions. Issue 1 (24th October 2017) - Newell, Bryce Clayton
ABSTRACT: This poster presents some initial findings from a mixed‐methods study of police officer attitudes and concerns about bystander (citizen) video and the officers' own use of body‐worn cameras (BWCs) within two municipal police agencies in the United States. Utilizing a data analysis methodology based in grounded theory, I argue that officers' concerns stem from their perceived inability to control context (both of what is recorded and/or disseminated, as well as the physical situations in which the recordings are made) and unwanted visibility. These concerns are heightened by the fact that officers are working in an environment filled with increasing calls to "release the tapes" (and thus to hold officers accountable for misconduct), especially because these calls are often based on assumptions about the "objectivity" of these visual records of police‐civilian interactions that run counter to many officers' opinions that the video evidence lacks vital contextual information.